Game accessibility: Adaptation of a digital escape room game to improve spatial cognitive skills on blind people - Coronado, Angelo; Carvalho, Sergio; Berretta, Luciana (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2023: Anais do XXV Simpósio de Realidade Virtual e Aumentada, 2023)
There is a concept called "Universal Accessible Games" that promotes the creation of games for everybody. To be more precise, games should be accessible for all gamers through inclusive design. Therefore, this work has the intention to adapt an Escape-the-room game to be accessible for completely blind people using game accessibility guidelines obtained in a Systematic Mapping. In addition to adapting a game, the work also aims to show a connection between playing an accessible escape-the-room game and enhancing the spatial cognitive skills of blind people. Finally, the work presents 35 accessibility guidelines from the literature for adapting a video game; and after user testing, it shows the potential value of an escape-the-room game for reaching accessibility and also training spatial cognitive skills.